THE IDEOLOGICAL TRANSFORMATION OF JAM'IYAH RIFA'IYAH IN DETERMINING THE QIBLA DIRECTION IN ADINUSO BATANG VILLAGE - Ikbal, Muhammad (Al-Hilal: Journal of Islamic Astronomy, 2022)
Technological developments make it easier for people to find the Qibla direction. However, the definition of the direction facing the Qibla which is varied according to fiqh causes public understanding of determining the direction of Qibla to be crowded into question. The concept of facing the Qibla taught by Ahmad Rifai in the Absyar book requires us to face the 'ayn al-ka'bah. This article discusses the concept of Qibla direction according to Ahmad Rifa'i and how the people of Adinuso-Batang Village respond to this thought. This article uses descriptive-qualitative method. This article finds that Ahmad Rifa'i's concept of Qibla direction is not in accordance with scientific theory and people prefer the results of scientific calculations over the results of their thoughts.